Seasonal shift of the gut microbiome synchronizes host peripheral circadian rhythm for physiological adaptation to a low-fat diet in the giant panda - Huang, Guangping; Wang, Le; Li, Jian; Hou, Rong; Wang, Meng; Wang, Zhilin; Qu, Qingyue; Zhou, Wenliang; Nie, Yonggang; Hu, Yibo; Ma, Yingjie; Yan, Li; et al. (Cell reports (Cambridge), 2022)
Characteristics of the gut microbiome vary synchronously with changes in host diet. However, the underlying effects of these fluctuations remain unclear. Here, we performed fecal microbiota transplantation (FMT) of diet-specific feces from an endangered mammal (the giant panda) into a germ-free mouse model. We demonstrated that the butyrate-producing bacterium Clostridium butyricum was more abundant during shoot-eating season than during the leaf-eating season, congruent with the significant increase in host body mass. Following season-specific FMT, the microbiota of the mouse model resembled that of the donor, and mice transplanted with the microbiota from the shoot-eating season grew faster and stored more fat. Mechanistic investigations revealed that butyrate extended the upregulation of hepatic circadian gene Per2, subsequently increasing phospholipid biosynthesis. Validation experiments further confirmed this causal relationship. This study demonstrated that seasonal shifts in the gut microbiome affect growth performance, facilitating a deeper understanding of host-microbe interactions in wild mammals. [Display omitted] •Giant pandas gain more body mass when eating shoots compared with leaves•More SCFAs are produced by the giant panda gut microbiome in the shoot-eating season•GF mice receiving the panda microbiota from the shoot-eating season gain more fat•Butyrate can synchronize host hepatic circadian rhythm to increase lipid production Huang et al. reveal that the gut microbiome can confer a plastic physiological response to seasonal diet shifts in the giant panda via synchronizing host peripheral circadian rhythm. The study sheds light on the causal relationships between the gut microbiome and host phenotype, providing potential avenues to improve host fitness.